(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to measure the impact of the quality of the audit on the Earnings Quality, for a sample of private joint stock companies listed on the Iraq Stock Exchange, as the research sample included (14) private and listed joint stock companies in issuing their financial statements for the period from (2010-2018), as well as companies The audit offices in charge of auditing these companies, which number (18) companies or an audit office, and the research relied on two main models for measurement, as the first model reflects the assumed relationship between independent variables represented in the characteristics of external audit quality and measuring the extent of its impact on the dependent variable represented in the Earnings Quality, As for the second model, it was adopted on the model (Jones, 1999) modified by (Dechow et al. ,1995) to measure the Earnings Quality by measuring the total, optional, and non-optional dues. The presence of quality auditing for audit firms and audit firms that audited the research sample companies and there are statistically significant indications about the practice of some Iraqi companies listed on the Iraq Stock Exchange for profit management But in varying proportions and the absence of a statistically significant impact of the auditing quality metrics on the Earnings Quality in companies listed on the Iraq Stock Exchange.